Criminological Activity of Forensic Science Institutions: the Concept of Implementation in Ukraine - Filipenko, Nataliia; Spitsyna, Hanna (Teisė, 2022)
The article analyzes the conceptual principles, opinions and ideas for understanding the essence of forensic science private theory, namely: forensic prevention concept is considered. The empirical prerequisites for the emergence and development of forensic research have been investigated: accumulation of empirical facts in the theory of forensic science and other sciences, manifestation of integration processes. Theoretical and applied foundations of expert prevention private theory are formulated.
Keywords: Prevention; criminalistics; forensic science; forensic prevention; forensic science general theory; forensic prevention private theory; specific expertise; forensic institutions; expert